6 - Health Inequality in South Africa: A Systematic Review - Chinwe C. Obuaku-Igwe (African Sociological Review, 2015)
This study presents a review of key empirical studies on health inequalities in South Africa with the aim of contributing to a comparative examination of social inequalities in health across different countries in Europe and other parts of the World. Studies reviewed were identified through a computerised search of key words such as inequalities, health, health inequalities, race, health in South Africa, health systems, socio-economic determinants of health and livelihoods in South Africa. Studies were included if the primary objective was to explore health inequality as a variable in child/adult mortality.